Healthy Eating: Salad Suggestions - Jennifer Hillan; Emily Minton (EDIS)
Salads are quick and easy to make and have endless possibilities! Paired with whole grain crackers or whole wheat bread, salads make healthy and convenient meals. Try some of the ideas this revised 2-page fact sheet for your next salad. Written by Jennifer Hillan and Emily Minton, and published by the UF Department of Family, Youth and Community Sciences, October 2011.